2021
DOI: 10.3390/ijms222111963
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Post-Transcriptional Regulation of Protein Expression in the Development of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is an incurable and prevalent respiratory disorder that is characterized by chronic inflammation and emphysema. COPD is primarily caused by cigarette smoke (CS). CS alters numerous cellular processes, including the post-transcriptional regulation of mRNAs. The identification of RNA-binding proteins (RBPs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) as main factors engaged in the regulation of RNA biology opens the door to understanding their role in coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 236 publications
0
3
0
1
Order By: Relevance
“…In an animal model of asthma, miRNA‐21 was expressed in the airway wall 34 . This molecule also plays a regulatory role in the pathophysiology of airway hyperresponsiveness and remodeling in the respiratory system such as COPD, but the specific mechanism is still poorly understood 30,35 . Besides, the effect of miR‐21 on airway epithelial cells in respiratory diseases has been studied in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of asthma, miRNA‐21 was expressed in the airway wall 34 . This molecule also plays a regulatory role in the pathophysiology of airway hyperresponsiveness and remodeling in the respiratory system such as COPD, but the specific mechanism is still poorly understood 30,35 . Besides, the effect of miR‐21 on airway epithelial cells in respiratory diseases has been studied in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…34 This molecule also plays a regulatory role in the pathophysiology of airway hyperresponsiveness and remodeling in the respiratory system such as COPD, but the specific mechanism is still poorly understood. 30,35 Besides, the effect of miR-21 on airway epithelial cells in respiratory diseases has been studied in previous studies. Li X et al reported that miR-21-5p-containing exosomes, produced by rat alveolar macrophages, transported miR-21-5p to tracheal epithelial cells and promoted epithelial mesenchymal transition (EMT).…”
Section: Microscopic Staining Analysismentioning
confidence: 99%
“…Another observation from our study is the discrepancy in transcript versus protein expression in peripheral lung tissue from non-COPD patients and COPD patients. Whether these discrepancies can be explained by (smoking-induced) changes in post-transcriptional 63 , remains to be established. Additional explanations could be the low number of patients included in the study and the biological variation.…”
Section: Discussionmentioning
confidence: 99%
“…unheilbar. [1][2][3] Das Prinzip, chemische Reaktionen durch Licht zu initiieren, ist bereits aus der Natur bekannt. Die Photosynthese stellt beispielsweise die Umwandlung von Sonnenlicht durch Pflanzen, Algen und einige Bakterienarten in chemische Energie dar, die für den Stoffwechsel und das Wachstum der Organismen notwendig ist.…”
unclassified